A Study on Regional Government Innovation: An Innovation Study of the Poverty Alleviation Program in West Bandung Regency - Suhendar, Atep; Anwar, Ali; Suryadi, Soleh (Technium Social Sciences Journal, 2025)
This study is conducted to address three research questions and explain the study's focus, namely: (1) the process of innovation program development; (2) the innovation capacity of the local government; and (3) the construction of an effective and efficient local government innovation model. This study applies a qualitative approach, where data was collected through interviews, observation, and documentation, using a spiral model of data analysis. The study finds that (1) the process of developing the poverty alleviation innovation program occurs through political (regulatory function) and managerial (management process) channels, which have been conducted innovatively; (2) there are four elements of innovation capacity analyzed, namely the innovative leadership of the Regent, implementing apparatus, budget, and program regulations. Innovation capacity is highly influenced by the Regent's leadership initiative and innovation is highly dependent on the budget (Regional/National Budget), while other capacity elements remain weak. Finally, a research recommendation is formulated, stating that the development of poverty alleviation innovation programs must be supported by innovative political and managerial processes. Innovation programs can originate from the government's internal or external partners through adoption with a replication strategy. Local government innovation policies and programs can be effective in both the short and long term if they are based on an innovation capacity that includes innovative leadership, quality of the work team, strong structures and systems, and the ability to manage external influences, all framed within a national innovation policy and program design.